Postwar Soldier Settlement - Black, John D.; Hyson, Charles D. (Quarterly Journal of Economics, 1944)
Scope of the paper, 1. — Historical background, 2. — Experience after World War I: United States, 4; Canada, 6; Australia, New Zealand, United Kingdom, 8. — Resettlement and rehabilitation in the United States: unemployment, 9; rural distress, 10; the Farm Security Administration projects, 11. — Other FSA opportunities: rehabilitation loans, 16; tenant purchase loans, 16. — The new legislation: Canada, 17; New Zealand, 20; United States, 20. — Limited value of certain provisions of the "G. I. Bill": present owners, 22; prospective tenants, 24; prospective buyers, 24. — The legislative background: United States, 27; Canada, 28. — Need for soldier settlement, 29. — Loan values, 31. — Tenant purchase as an alternative, 33. — Concluding remarks, 34.